Inklusi dan diferensiasi dalam pendidikan agama islam: Menanggapi keberagaman peserta didik di MAN 3 Sukabumi - Ubaidillah Ubaidillah; Mulyawan Safwandy Nugraha (Jurnal Inovasi Pembelajaran dan Pendidikan, 2025)
This study examines the implementation of inclusion and differentiated learning in Islamic Religious Education (PAI) as a response to student diversity at MAN 3 Sukabumi. Islamic education in madrasahs often relies on rigid standardization, which risks neglecting students’ diverse learning needs, readiness levels, and backgrounds. Using a qualitative approach with a descriptive case study design, data were collected through participatory classroom observations, in-depth interviews with PAI teachers, and document analysis of lesson plans and assessment instruments. The findings indicate that inclusion at MAN 3 Sukabumi is not merely a technical arrangement but represents a paradigm shift in teachers’ perspectives toward diversity as a pedagogical asset and a reflection of Islamic justice (‘adalah). Differentiation in content, process, and product enables proportional access to religious knowledge and values for students with varying abilities. However, challenges remain, particularly related to large class sizes and administrative demands. This study concludes that strengthening teachers’ capacity in differentiated instructional design is essential for developing inclusive, humane, and equitable Islamic education in madrasahs.